Military and political aspects of one of the problems of the modern power industry - Gurevich, V. (Електротехніка і електромеханіка, 2015)
The problem of Intentional Destructive Electromagnetic Impacts (IDEI) on power systems has become recently more and more actual in connection with two modern trends: the extension of using microelectronics and microprocessor-based devices and systems in electric power industry – on the one hand, and the intensive design of special equipment for distance destruction of electronic devices and systems – with another. The most powerful method for such destruction is the High-altitude Electromagnetic Pulse (HEMP) as a result of a high-altitude nuclear explosion. The history of experimental high-altitude nuclear explosions has been known now for over half a century. During this time quite a few scientific articles and books presenting details of this phenomenon and measures of protection from it have been published. In view of this fact, it would be possible to assume that the problem of protection against HEMP has been solved for a long time and modern power systems are well protected from this phenomenon. However the research performed by the author displays that actually it has not and for the past decades in one country of the world, at least, no practical measures have been taken for the protection of the national infrastructures against HEMP and all action has been restricted only to writing reports, recommendations and guidelines. In the paper the reasons for such situation (in particular, political and military aspects of the problem) are analyzed.